2022
DOI: 10.1051/kmae/2021038
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fish diversity of Chicago's waterways

Abstract: Descriptions of shifts in biodiversity across time are desired for urban freshwater systems to better study ecosystem change and causal mechanisms. I document changes in fish diversity within the Chicago Area Waterways across 35 years using a battery of diversity metrics calculated on both abundance and biomass data. Has diversity of Chicago's waterways changed over 35 years and if so, do different diversity metrics exhibit different trends or breakpoints in trends? Diversity of the fish assemblage increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…We found that Bluntnose Minnow populations increased in abundance, biomass, and individual size. Similarly, abundance and biomass of several other minnow species also increased in the CAWS (Happel, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We found that Bluntnose Minnow populations increased in abundance, biomass, and individual size. Similarly, abundance and biomass of several other minnow species also increased in the CAWS (Happel, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Water quality of the system increased following these improvements and led to lower concentrations of wastewater related contaminants now compared to the 1980s (Happel & Gallagher, 2022; Pluth et al, 2021). Within the CAWS, fish species richness, diversity, abundance, and biomass have increased steadily since 1985 (Happel, 2022; Happel & Gallagher, 2021). Reductions in wastewater contaminants and increases in wastewater storage capacities were better predictors of increases in species richness over various weather and water quality (i.e., temperature, pH, dissolved oxygen) parameters (Happel & Gallagher, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoreline armouring amounts differ across the system (Table 1 and Figure 1 The CAWS fish community is numerically dominated by gizzard shad (Dorosoma cepedianum) and common carp (Cyprinus carpio), who alone account for nearly half of the fish in the system (Happel, 2022;Happel & Gallagher, 2021). The next four most abundant species help account for a further 20%-25% of the individuals, and the nine most abundant species account for 80%, leaving 20% of the total fish in the system spread across some 63 species' abundances.…”
Section: Study Systemmentioning
confidence: 99%